#145 Formulation and evaluation of orodispersible tablets of Trimethobenzamide HCl - Garg, Sakshi; Lakshmi (Journal of Pharmaceutical Chemistry, 2022)
Orodispersible drug delivery system has shown bioavailability of drug significantly greater than conventional drug delivery system and dissolves rapidly in saliva without the need of water. Trimethobenzamide HCl is an anti-emetic drug and acts within the central nervous system to inhibit the medullary chemoreceptor trigger zone by blocking emetic impulses (dopaminergic) to the vomiting center. The present research work was an attempt to develop orodispersible tablets of Trimethobenzamide HCl with the aim of rapid therapeutic effect with good mouth feel and to enhance patient compliance. The preformulation studies included FTIR, and DSC of the drug was carried out to study the behavior of the drug. The drug excipient compatibility showed no significant interaction between drug and excipients used in the formulation. The tablets were formulated by wet granulation method using Crosspovidone as a super disintegrant and Poly vinyl pyrrolidine as a binder to provide faster disintegration and drug release. 32 full factorial design was performed to study the effect of the formulation variables (Crosspovidone and Mannitol) on disintegration time. Tablets were evaluated for their morphology, micromeritics properties, drug content, wetting time, water absorption ratio, disintegration time, and dissolution studies. Numerical optimization was performed to find the optimum composition, and based on this; an optimized formulation was selected. Optimization studies showed that the extra design check point formulation (F10) matched closely with optimized formulation (F3) with a similarity factor of 96.89%. Kinetic studies for in vitro drug release followed Korsmeyer’s–pepp as a model. Disintegration time of optimized formulation was found to be 26 sec with 99.51% of drug release within 15 min. Finally, it was concluded that the developed orodispersible tablets for Trimethobenzamide HCl could be a promising system for rapid action, good mouth feel as well as better patient compliance.